Internet impropriety: Moral identity, moral disengagement, and antisocial online behavior within an early adolescent to young adult sample. Issue 2 (7th November 2022) - Saulnier, Luc; Krettenauer, Tobias
Abstract: Introduction: Information and Communication Technologies (ICT) are the most popular medium for social communication amongst adolescents and young adults. However, there is growing concern surrounding heightened ICT use and the activation of influential social constructs such as moral identity and moral disengagement. The importance of moral ideals to oneself (i.e., moral identity) and the distancing of oneself from these moral ideals (i.e., moral disengagement) are often contextual and were tested for differences in online domains compared to face‐to‐face interactions. Methods: Three hundred and ninety‐two early adolescent to young adult participants ( M age  = 19.54 years, SD = 4.48) completed self‐report questionnaires that assessed online and face‐to‐face behavior in this cross‐sectional study. Results: Moral identity in an online context was significantly lower when compared to family and friend contexts. Further, moral disengagement was significantly higher in an online context when compared to face‐to‐face contexts and online moral disengagement significantly mediated the relationship between online moral identity and antisocial online behaviors (i.e., pirating, trolling, and hacking, etc., ). Both of these contextual differences remained stable across early adolescence to young adulthood. Conclusion: Moral identity and moral disengagement exhibit sociocognitive effects within online contexts across ages of early developmental importance. These results may account for high prevalence rates of antisocial online behavior such as trolling, pirating, and hacking within this sample. As social interaction for younger demographics continues to gravitate online, these results highlight that online contexts can influence important personality constructs.